Marina Aromsztam – rosyjski pedagog innowator - Jeleńska , Weronika (Studia Edukacyjne, 2021)
The article introduces the Russian pedagogue Marina Aromshtam, whose contribution to modern, post-Soviet pedagogy gives her a special significance in contemporary science. Her activity at school has been illustrated by examples of two outstanding works Like a Diary. Teachers’ Stories and When Angels Rest. The writer’s detailed biography helps to show in detail a number of changes and innovations which, thanks to her numerous articles and books, have influenced many people. Importantly, it has revived the practice of family reading, strongly involved parents in the education of their children, and has disseminated knowledge about the world among readers large and small. As a strong woman, she made significant changes in contemporary pedagogy and became a true patron of children’s education.